Who replies to consultations, and what do they say? The case of broadband universal service in the UK - Volker Stocker; Jason Whalley (International Telecommunications Society (ITS), 2017)
Over the last decade or so, access to broadband telecommunication services has become increasingly important. Through broadband, households and companies are able to engage with the informationbased economy that is emerging, through, for example, buying and selling online or using social media. While many in the UK already benefit from the provision of broadband, some do not – they may not be able to access the Internet and when they do, their connection may be poor. After trying to resolve this through a stream of different initiatives, the UK government announced a broadband universal service obligation of 10 Mbps in late 2015. Ofcom, the telecommunications regulator, launched a consultation in April 2016 and sought the views of interested parties. The consultation attracted considerable interest, but after the submissions from orchestrated campaigns are discounted just over 100 responses remain. But who contributed and what did they say? To explore these two questions, this paper adopts a qualitative approach, using NVIVO, to analyse the responses to the consultation. Our analysis found that submissions were made by individuals as well as pressure groups, companies and various levels of government. Their contributions were highly diverse, reflecting both the complexity of the issue as well as its politicised nature. Somewhat surprisingly, most of the responses address only some of the issues raised in Ofcom's consultation document, and tensions and contradictions can be identified between the different responses. There is, to a lesser or greater extent, a lack of agreement among the responses regarding the appropriateness of 10 Mbps, whether this should change in the future, how it should be funded and what technologies should be used. In other words, we found no agreement on the key issues that need to be resolved if everyone in the UK is to have access to broadband.
Keywords: 330; universal service; broadband; Internet access; consultation; UK